Functional constipation in children; changing clinical spectrum with unusual presentation: A case report - Bharti, Laxmi Kant; Kumar, Basant (Indian Journal of Case Reports, 2019)
Constipation in children is progressively increasing day by day because of changing lifestyle and dietary intake. Sometimes, functionalconstipation cases are misdiagnosed as functional abdominal pain because of inappropriate history and examination. We present an8-years-old boy with a history of intermittent moderate to severe abdominal pain for 2 months. Basic blood investigations andultrasound of the abdomen were normal, surprisingly, X-ray of the abdomen revealed the diagnosis. Simple X-ray erect abdomen isvery useful in a special situation for the diagnosis of functional constipation.